Study of biological properties of Lactobacillus helveticus strains isolated in the Karaganda region for the design of the consortium - Amirkhanova, Zh.T.; Bodeeva, R.T.; Akhmetova, S.B.; Kushugulova, A.R. (KSU Publ., 2020)
In the leading scientific centers of the world, research in the field of microbiology of dairy products for healthy nutrition production and probiotics containing live cultures of lactic acid bacteria, which are antagonists of various representatives of opportunistic-pathogenic and pathogenic microflora of the human intestinal tract, becomes particularly relevant. The effectiveness of probiotic preparations and products of milk functional nutrition depends primarily on the properties included in their species of different strains of bacteria. In this connection, at present the priority is given to the study of lactic acid strains isolated from natural sources, having high probiotic activity. One of the main components of starter cultures for dairy products and probiotic drugs is most often bacteria of the genus Lactobacillus. This article presents the study of morphological, culture properties, acid-forming ability, antibiotic sensitivity Lactobacillus helveticus isolated in the Karaganda region, having antagonistic activity towards test strains: Staphylococcus aureus NCTC 12973/ATCC ® 29213 ™, Escherichia coli NCTC 12923/ ATCC® 8739™, Salmonella typhimurium NCTC 12023/ ATCC® 14028™, Pseudomonas aeruginosa NCTC 12903/ ATCC® 27853™, Klebsiella pneumonia NCTC 9633/ ATCC® 13883™. The use of modern microbiological methods allowed screening of isolated cultures and selecting of biological active strains: Lactobacillus helveticus-17, Lactobacillus helveticus-20, Lactobacillus helveticus-14, Lactobacillus helveticus-15. According to the obtained results, strains Lactobacillus helveticus promising applicants for the consortium Lactobacillus spp. And it makes possible to judge the competitiveness of these strains.
Консорциум дизайны үшін Қарағанды облысынан бөлінген Lactobacillus helveticus штамдарының биологиялық қасиеттерін зерттеу
Изучение биологических свойств штаммов Lactobacillus helveticus, выделенных в Карагандинской области для дизайна консорциума
Keywords: cultivation; strain; Gram color; Lactobacillus helveticus; antagonistic activity; acid formation activity; antibiotic sensitivity